The WTO and technical barriers to trade - Henson, Spencer; Wilson, John S. (Cheltenham, UK ; Northampton, Mass. : E. Elgar pub., 2005)
This authoritative volume brings together for the first time the foremost research and commentary on technical barriers to trade. It explores the major theoretical issues associated with analysis of the impact of technical measures on trade in goods and the challenges associated with attempts to quantify impacts on trade flows. Previous empirical analyses of the impact of technical barriers on trade in goods in general are then presented. This is followed by in-depth coverage of the trade effects of sanitary and phytosanitary (SPS) measures, an area where analysis is particularly challenging. Finally, the volume concludes by exploring institutional efforts to overcome the impact of technical barriers, including harmonization of standards and the role of the WTO. The WTO and Technical Barriers to Trade will be an invaluable source of reference for academics, students and policymakers alike
Includes bibliographical references and index.
lje 23/08/16
Loan
Keywords: Non-tariff trade barriers; International trade